No matter what - Gliori, Debi. (San Diego : Harcourt Brace, 1999)
Small, a little fox, seeks reassurance that Large will always provide love, no matter what.
Keywords: Parent and child -- Fiction; Love -- Fiction; Foxes -- Fiction; Stories in rhyme